2005
DOI: 10.1007/s00040-005-0803-3
|View full text |Cite
|
Sign up to set email alerts
|

A new type of male dimorphism with ergatoid and short-winged males in Cardiocondyla cf. kagutsuchi

Abstract: A new type of ant male dimorphism, consisting of wingless (ergatoid) and short-winged (brachypterous) males, was found in a species of the "Cardiocondyla kagutsuchi"-complex from Malaysia. The ergatoid males show the typical morphological and behavioral characteristics of those of many other Cardiocondyla species. The brachypterous males are morphologically intermediate between ergatoid males and typical winged males of other taxa in this genus. On one hand, they share a number of morphological and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Yamauchi et al (2005) found that intermorphic males of C. cf. kagutsuchi that eclose in the presence of adult rivals have a significantly higher survival rate than wingless males.…”
Section: Resultsmentioning
confidence: 99%
“…Yamauchi et al (2005) found that intermorphic males of C. cf. kagutsuchi that eclose in the presence of adult rivals have a significantly higher survival rate than wingless males.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of C. cf. kagutsuchi with “intermorphic” males combining the morphological traits of wingless fighter males and wings suggests that male‐determining mechanisms are not very stable in this taxon (Yamauchi et al 2005). In addition, the high proportion of “sex mosaics” in one C. cf.…”
Section: Resultsmentioning
confidence: 99%
“…Male wing dimorphisms are observed in many species of Cardiocondyla ants, and several patterns of male dimorphisms have been observed, such as the combination of winged and ergatoid males or of brachypterous and ergatoid males, and only ergatoid males (e.g., Bolton, 1982;Kugler, 1983;Seifert, 2003;Yamauchi et al, 2005). In C. obscurior, under good conditions, colonies start to produce ergatoid males, whereas under poor conditions, winged males are produced Heinze et al, 2004;Du et al, 2007;Schrempf and Heinze, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Cardiocondyla includes myrmicine ant species that exhibit male dimorphism, with both winged and wingless males (Kugler, 1983;Heinze et al, 1998;Terayama, 1999;Seifert, 2003;Yamauchi et al, 2005). The wingless males are referred to as ''ergatoid'' males due to their very similar external morphologies to workers.…”
Section: Introductionmentioning
confidence: 99%